ANALISIS PREFERENSI WISATAWAN DALAM PEMILIHAN PRODUK WISATA UNTUK PERENCANAAN AGROWISATA PIAT MANGUNAN-GIRIREJO UNIVERSITAS GADJAH MADA - Jefry Ivandony Wahyu Gusti; Esa Riandy Cardias (Jurnal Manajemen Perhotelan dan Pariwisata, 2022)
The Mangunan-Girirejo UGM Agro Technology Innovation Center (PIAT Magir UGM) has its own natural and cultural attractions that have the potential to become an education-based agro-tourism, as well as one of the agro-tourism with an icon in the form of 3S fruit plants (sapodilla, soursop, srikaya). The purpose of this research is to examine tourist preferences for potential tourism products in order to plan agro-tourism at PIAT Magir UGM. The quantitative descriptive method was used, along with cross-tabulation analysis and the Chi-Square Test. To determine the type of respondents, 123 visitors to the Mangunan tourist area and tourists who had visited agro-tourism were chosen using the accidental purposive sampling technique. The study's findings show that: (1) PIAT Magir UGM has a variety of potential tourism products that can be developed for agro-tourism planning; (2) Tourists who travel to agro-tourism are mostly tourists in the age group of 26-33 years (63.4%), which age group is categorised as the millennial generation; (3) Tourist preferences for tourism product components that have a significant relationship are tourists in the age group 26-33 with tourist attractions in the form of festivals/events, accessibility in the form of riding a bicycle to go around agro-tourism, and amenities in the form of camping accommodation and welcome gate designs in the form of fruit statues of agro-tourism icons.